DISMIC AND SOLUTIONS TO YOUNG PEOPLE IN THE PREPARATION OF YOUNG PEOPLE - Izzattullayeva Zohida Sunnatdullayevna (Journals Park Publishing, 2024)
In the article, we will consider ways to find some problems and their solutions of young people, and their solutions to problems. We will try to discuss the consequences of the reasons why it has become an early salary between our people today. We also touch the fact that the country needs an early marriage and divorce, and it is also necessary to divorce, and how it is recommended by many psychologists and what they are recommended by many psychologists. The most important task is to preserve the peace of young families, which are corrupted in modern difficulties and stress, to preserve the peace of young families, which are corrupted in modern difficulties and stress. Especially during the preparation of young people for family life, difficulties and uncertainties on the path of personal maturity are becoming more important. Let us consider young people to find out the way they find reasonable solutions to problems based on their adolescence and analysis of the psychologists of our psychologists in preparing them.
Keywords: family support, communication, emotional durability, mental treatment, youth, your psychologist, development, adaptation, perseverance, determination.